Penerapan Metode WASPAS dalam Seleksi Calon Kandidat Ketua Palang Merah Remaja - Lathifah (CV. Keranjang Teknologi Media, 2024)
The selection of candidates for the Chairman of the Youth Red Cross (PMR) is an important step in ensuring that individuals holding such positions have abilities and commitments that are in accordance with the human values and mission of the organization. One of the main issues in the election of the Chairman of the Youth Red Cross (PMR) is often related to transparency, fairness, and active participation of the PMR members themselves. Sometimes, the electoral process can be subjective or influenced by personal preferences, which can reduce the trustworthiness and credibility of the election. The application of the Weighted Aggregated Sum Product Assessment (WASPAS) Method in the selection of candidates for the Chairman of the Youth Red Cross (PMR) is a careful and effective step in selecting leaders who best suit the needs of the organization. This research was conducted to determine candidates for the head of the Youth Red Cross by applying the WASPAS method so that it will help in making a decision. The results of the selection of prospective candidates using the WASPAS method recommended Ahmad's name with a final score of 2.918120014 to get 1st place, Jayanto name with a final score of 2.905182843 to get 2nd place, and Yudha name with a final value of 2.890055868 to get 3rd place.